Pengaruh Work Life Balance terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Tanjung Selatan Makmur Jaya - Firdaus, Firdaus (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
This study aims to analyze the effect of work-life balance on employee performance, with job satisfaction as an intervening variable at PT. Tanjung Selatan Makmur Jaya. Work-life balance is an essential factor in enhancing employee productivity, as the balance between work and personal life influences employee well-being. Additionally, job satisfaction is identified as a mediating variable in the relationship between work-life balance and employee performance. The research method used is quantitative with an explanatory research approach. Data were collected through questionnaires distributed to 141 employees of PT. Tanjung Selatan Makmur Jaya. Path analysis was used to examine both direct and indirect relationships among the variables. The results show that work-life balance has a positive and significant effect on employee performance. Furthermore, job satisfaction also mediates the effect of work-life balance on employee performance. This indicates that the better the work-life balance perceived by employees, the higher their job satisfaction, which ultimately positively impacts employee performance. This study suggests that companies should pay more attention to work-life balance policies that can enhance job satisfaction and employee performance, such as flexible working hours and effective workload management.